Analysis of Farmers Attitude In Cenning And Bululawang Sugarcane Business Variety - Budi Utomo; Teguh Soedarto (Agricultural Science, 2022)
This study was conducted to determine the differences in income, level of feasibility and level of enthusiasm or attitude of farmers in cultivating sugarcane varieties of Cenning and Bululawang. The research was carried out in Badang Village, Ngoro District, Jombang Regency from May to July 2021. The research method used was descriptive analysis method, which means analyzing income that has been ongoing or based on reality. In addition, the multi-attribute fishbein model is also used to calculate the interest or attitude of sugarcane farmers to plant cenning and Bululawang varieties.The results showed that the income obtained from sugarcane farming of the Cenning variety was Rp. 24.522.620,- while the sugarcane of Bululawang variety was Rp. 18.438.820,-. Sugarcane farming of the cenning variety in Badang Village, Ngoro District, Jombang Regency is feasible to be cultivated with an R/C Ratio of 1.61. Meanwhile, the Bululawang variety of sugarcane farming is also feasible with an R/C Ratio of 1.49. Based on fishbein analysis, it was found that the attitude of sugarcane farmers in Badang Village, Ngoro District, Jombang Regency (Ao) towards the cenning variety was 37,28. It is interpreted that the farmer's total attitude (Ao) towards the cenning variety is in the third range (36-51) which is agree (S). So it can be concluded that sugarcane farmers in Badang Village, Ngoro District, Jombang Regency prefer cenning sugar cane to Bululawang sugarcane varieties.